Students’ Preferred Characteristics of Learning Environments in Vocational Secondary Education - Placklé, Ingeborg; Könings, Karen D.; Jacquet, Wolfgang; Struyven, Katrien; Libotton, Arno; van Merriënboer, Jeroen J. G.; Engels, Nadine (International Journal for Research in Vocational Education and Training, 2014)
If teachers and teacher educators are willing to support the learning of students, it is important for them to learn what motivates students to engage in learning. Students have their own preferences on design characteristics of powerful learning environments in vocational education. We developed an instrument - the Inventory Powerful Learning Environments in Vocational Education - to measure students’ preferences on characteristics of powerful learning environments in vocational education. We investigated whether student preferences on the design of their learning environments are in line with what is described in the literature as beneficial for learning. Data of 544 students show that the preferences of students support most characteristics of PLEs in vocational education. Looking through the eyes of students, teachers have to challenge their students and encourage them to take their learning in their own hands. Adaptive learning support is needed. Remarkable, students do not prefer having reflective dialogues with teachers or peers.